The Influence of Educational Employees’ Policy Alienation on Their Change Cynicism: An Investigation in the Turkish Public-Schooling Context - Tijen Tulubas (Educational Process: International Journal)
Background/purpose – Policy alienation is considered to be significant for successful policy implementation and is linked to public professionals’ attitudes towards change. The current study was conducted to investigate the influence of educational employees’, namely teachers’ and school administrators’, policy alienation on their change cynicism in the context of Turkish public-schools.